Busana Pesta dengan teknik Pattern Magic (The knot dress) dan hiasan Tenun Tapestry - Nashikhah, Ma'rifatun Ifa; Inayah, Desy Tri; Widyastuti, Ika Zuli (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2021)
Patterns are not only needed in the manufacture of individual fashion but a pattern has grown in all the industrialized worlds, home industry, convection and garment. In japan, pattern magic was present as solutions to a deficiency of the flat pattern. The pattern magic is development from formulation that inspired by the environment. The patterns can be separated from the influence of technology and the around of environment. The results of this study aims to combine a pattern magic and trimmings woven tapestry in evening gown thant given a new element in fashion. Because generally tapestry is used as wall hangings and household. Beside that, lifestyle some people want to be perform different with others. Exploration pattern magic can make an enormous impact and more value, As the fashion industry, it is a new invention that can become global trend in the community. The results of evening gown with pattern magic (the knot dress) and tapestry show that pattern magic on evening gown is eficien because this pattern asamble with dress and doesn’t need another pattern to make hiasan pesta, so pattern of an ornament ribbon not separated with dress pattern